REVIEW OF VICTIMOLOGY OF VICTIMS OF THEFT IN THE CRIMINAL JUSTICE SYSTEM - Rhendy Ahmad Fauzi (Universitas Labuhanbatu, 2023)
Victimology, from the word victim (victim) and logi (science), Latin victima (victim) and logos (science). In simple terms, victimology means the science of victims (crimes). According to the Crime Dictionary, which is quoted by an Abussalam expert, the victim is